2015
DOI: 10.1159/000381706
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Arterial Hemodynamic in Ischemic Levkoaraiosis Suggests Hypoperfusion Mechanism

Abstract: Background: Leukoaraiosis (ILA) is believed to be ischaemic in origin due to its similar location as that of lacunar infarctions and its association with cerebrovascular risk factors. However, its pathophysiology is not well understood. The ischaemic injuries may be a result of increased pulsatility or cerebral hypo-perfusion. We used carotid duplex ultrasound to prove that the underlying mechanism is hypo-perfusion. Methods: We compared 55 ILA patients to 44 risk factor-matched controls with normal magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…ILAi were therefore defined as the ratios between carotid stiffness parameters (PWVβ, Ep, β index) and blood flows in the ICA: Q-ICAd and Q-ICAm. 22 , 23 All the ILAi were higher in the ILA group compared to the control group ( P <0.01), the most significant was PWVβ/Q-ICAd ( P =0.001). The results are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…ILAi were therefore defined as the ratios between carotid stiffness parameters (PWVβ, Ep, β index) and blood flows in the ICA: Q-ICAd and Q-ICAm. 22 , 23 All the ILAi were higher in the ILA group compared to the control group ( P <0.01), the most significant was PWVβ/Q-ICAd ( P =0.001). The results are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 87%
“…The study was a post hoc analysis of our previous studies on carotid stiffness parameters and carotid hemodynamic in patients with ILA. 22 , 23 The subjects were included in the study based on the already performed brain magnetic resonance imaging (MRI). The patients with ILA were chosen among patients who have been treated in our outpatient clinic because of ILA and were up to 65 years old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many risk factors for CSVD, age and hypertension are the clearest risk factors. The incidence of WMHs increases with age, with an average age of 10 years and an increase of two to three times (Turk et al, 2015). Meanwhile, studies have found that the detection rate of LI at 60 years old is 6% to 7%, while the detection rate at 80 years old is increased to 28% (Vermeer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding of the CCH pathophysiology indicates that it is a disease defined by cerebral blood vessel infarction or angiostenosis, which causes an insufficient supply of glucose and oxygen to the central nervous system, leading to neuronal damage in the center and surrounding penumbra with a milder ischemic insult . The most recent research has shown that neuronal injury, induced by oxygen and glucose deprivation (OGD), is a very complex process with multiple mechanisms, including excitotoxicity, oxidative stress, apoptosis, and variations in gene expression or kinase activation . Given the close relationship between them, increasing attention has been focused on elucidating the underlying mechanism of CCH‐VD progression to provide promising therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%